A study of network characteristics in diffusion-based molecular communication - Jamar, Adeebah (2015)
Diffusion based Molecular Communication is the new communication paradigm in nanonetwork. Diffusion-based molecular communication use molecules for transmitting information in nanonetwork. Molecules propagate through the diffusion process under Fick’s Law. However, medium propagation or channel will affect the propagation of molecules from transmitter to receiver determine and hence the reliability of the system. In addition, molecules are diffused in unpredictable way in diffusion communication, making the system unreliable. In this thesis, medium concentration and velocity are characteristics that are studied in order to improve the performance of the diffusion communication network. The simulation result show that, control the medium concentration and velocity can improve the system performance. Results from simulations have also shown that, by using different shapes of topology as layout to place the nanomachines, the performance of the diffusion communication can be improved.